Augmented reality for NDT imaging - Tan, Si Hui (Nanyang Technological University, 2022)
Maintenance is frequently carried out by various industries to ensure the integrity of materials and structures in equipment, aircrafts, ships etc. Non-destructive testing (NDT) is a testing and analysis technique commonly used to check for the presence of any internal defects without causing damage to the original part. This project was carried out to develop an augmented reality application to improve the way the defects are presented in a 2-dimensional ultrasonic scan. The objective of this project is to find solutions to synchronize the physical part with software. The physical components used in this project are an ultrasonic PAUT probe, laptop, and Epson BT-300 AR glasses while the software consists of Wikitude, Unity and Miracast. For the augmented reality effect, the ultrasonic images from the PAUT probe that scans over the specimen are matched with Wikitude and Unity, and Miracast is utilized to show the augmented reality to the BT-300AR glass. The results obtained are discussed. There are also areas that can affect the outcome of the results. Lastly, some areas of improvement are also highlighted in this project.